2006
DOI: 10.1126/science.1127376
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Sustainability of a High-Energy, Low-Diversity Crustal Biome

Abstract: Geochemical, microbiological, and molecular analyses of alkaline saline groundwater at 2.8 kilometers depth in Archaean metabasalt revealed a microbial biome dominated by a single phylotype affiliated with thermophilic sulfate reducers belonging to Firmicutes . These sulfate reducers were sustained by geologically produced sulfate and hydrogen at concentrations sufficient to maintain activities for millions of years with no apparent reliance on photosynthetically derived substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
330
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(345 citation statements)
references
References 24 publications
10
330
0
5
Order By: Relevance
“…Recently, a study by Alawi et al (2011) identified sequences similar to Candidatus Desulforudis audaxviator in 61°C tempered fluid samples taken after heat extraction in the topside facility of a geothermal plant in the Molasse Basin (Germany). Candidatus Desulforudis audaxviator is a rarely detected microorganism so far, whereas it has the ability to subsist as a single species ecosystem that is based on hydrogen originating from radiochemical reactions in deep crustal rocks and sulfate reduction as the dominant electronaccepting process (Lin et al 2006;Chivian et al 2008). The repeated detection of sequences affiliated to this species in a saline aquifer of the NGB (TDS 130 g l -1 ) as well as in a low mineralized Malm aquifer of the Molasse Basin (TDS < 1 g l -1 ) indicates that this organism is much more distributed in the deep subsurface than previously assumed and co-existing with other SRB.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study by Alawi et al (2011) identified sequences similar to Candidatus Desulforudis audaxviator in 61°C tempered fluid samples taken after heat extraction in the topside facility of a geothermal plant in the Molasse Basin (Germany). Candidatus Desulforudis audaxviator is a rarely detected microorganism so far, whereas it has the ability to subsist as a single species ecosystem that is based on hydrogen originating from radiochemical reactions in deep crustal rocks and sulfate reduction as the dominant electronaccepting process (Lin et al 2006;Chivian et al 2008). The repeated detection of sequences affiliated to this species in a saline aquifer of the NGB (TDS 130 g l -1 ) as well as in a low mineralized Malm aquifer of the Molasse Basin (TDS < 1 g l -1 ) indicates that this organism is much more distributed in the deep subsurface than previously assumed and co-existing with other SRB.…”
Section: Discussionmentioning
confidence: 99%
“…Water properties measured on-site included temperature (>60ºC), pH (9.3), Eh (-330 mV), and dissolved oxygen (Lin et al, 2006). The dissolved-oxygen content of the initial sample was slightly above the detection limit of 1 μM (32 μg/L), but this might have been an artifact of the initial high flow rate given that subsequent samples had no detectable oxygen.…”
Section: Microbial Activity In the Deep Subsurfacementioning
confidence: 99%
“…At greater depths, microbial populations are not necessarily dependent on photosynthetically produced electron donors and acceptors (i.e., nutrients; Lin et al, 2006). The existence of microorganisms at depths greater than one kilometer is well established, but much remains unknown regarding the abundance and sustainability of these microbial communities.…”
Section: Microbial Activity In the Deep Subsurfacementioning
confidence: 99%
See 2 more Smart Citations